ECOLOGICAL EDUCATION OF THE POPULATION AS AN IMPORTANT COMPONENT OF ENVIRONMENTAL POLICY - Batyrbayev N.M. (Хабаршы. Заң сериясы, 2018)
This article analyzes the concepts and role of environmental education. Environmental education of the population.The purpose of this work is the analysis of scientific approaches to the concept of population. As well as an analysis of the role of the environmental consciousness of citizens in the modern world. Applied works are applied both by general theoretical and specifically scientific methods of knowledge, namely: dialectical, comparative legal, historical, formally dogmatic (specially legal), concrete legal and logical. The scientific and practical significance of the research lies in the results and conclusions.The article analyzes the conceptual apparatus and their interrelations, which also face state and hu-man rights organizations.The practical significance of the article lies in the possibilities of using the results obtained to im-prove the current environmental legislation of the Republic of Kazakhstan, as well as in the law enforcement activity of the authorized bodies in the field of ecology.